Viral-like symptoms induced by the ectopic expression of the p23 gene of Citrus tristeza virus are citrus specific and do not correlate with the pathogenicity of the virus strain - Fagoaga, Carmen; Lopez, C.; Moreno, Pedro; Navarro, Luis; Flores, R.; Pena, Leandro (2017)
Ectopic expression of the p23 gene from a severe (T36) strain of Citrus tristeza virus (CTV) induces viral-like symptoms in Mexican lime. Here, we report that expressing the same gene from a mild strain induced similar symptoms that correlated with accumulation of p23 protein irrespective of the source strain. CTV inoculation of transgenic limes showing CTV-like leaf symptoms and high p23 accumulation did not modify symptoms initially, with the virus titer being as in inoculated nontransgenic controls; however, at later stages, symptoms became attenuated. Transformation with p23-T36 of CTV-susceptible sweet and sour orange and CTV-resistant trifoliate orange also led to CTV-like leaf symptoms that did not develop when plants were transformed with a truncated p23 version. In transgenic citrus species and relatives other than Mexican lime, p23 was barely detectable, although symptom intensity correlated with levels of p23 transcripts. The lower accumulation of p23 in sweet and sour orange compared with Mexican lime also was observed in nontransgenic plants inoculated with CTV, suggesting that minimal p23 levels cause deleterious effects in the first two species. Conversely, transgenic expression of p23 in CTV nonhost Nicotiana spp. led to accumulation of p23 without phenotypic aberrations, indicating that p23 interferes with plant development only in citrus species and relatives.